Proceedings of the ACM SIGPLAN/SIGBED 2010 Conference on Languages, Compilers, and Tools for Embedded Systems 2010
DOI: 10.1145/1755888.1755910
|View full text |Cite
|
Sign up to set email alerts
|

Cache vulnerability equations for protecting data in embedded processor caches from soft errors

Abstract: Continuous technology scaling has brought us to a point, where transistors have become extremely susceptible to cosmic radiation strikes, or soft errors. Inside the processor, caches are most vulnerable to soft errors, and techniques at various levels of design abstraction, e.g., fabrication, gate design, circuit design, and microarchitecture-level, have been developed to protect data in caches. However, no work has been done to investigate the effect of code transformations on the vulnerability of data in cac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Both RVF and CVF values are calculated by considering susceptible times of register values and cache blocks respectively. [28] has also proposed a static analysis method to estimate program vulnerability in caches.…”
Section: Related Workmentioning
confidence: 99%
“…Both RVF and CVF values are calculated by considering susceptible times of register values and cache blocks respectively. [28] has also proposed a static analysis method to estimate program vulnerability in caches.…”
Section: Related Workmentioning
confidence: 99%
“…In this article, we present steady-state analysis of the data in the cache for several kinds of loops and increase the applicability and effectiveness of the PICA approach by answering the question of "when to prefetch." While there are elaborate analytical models on cache behavior [Chatterjee et al 2001;Ghosh et al 1997;Shrivastava et al 2010;Verdoolaege et al 2007], none of them are widely used today, as they have practical limitations, such as high computational complexity and limited architectural features supported. Moreover, our problem is more complex than cache modeling, because it also involves hardware prefetching and multiple processor states.…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies [22][23][24] have shown that implementing SEC-DED can increase L1 cache access latency by up to 95%, and power consumption by up to 22%.…”
Section: Avf-aware Ecc Techniquementioning
confidence: 99%
“…Moreover, protecting higher levels of cache (e.g., L1 data cache (L1D)) using ECC would induce higher overheads. Previous studies showed that single-error correction and doubleerror detection (SEC-DED) in L1 cache would increase its access latency by up to 95%, power consumption by up to 22%, and area cost by up to 18% [22][23][24] . A variety of techniques have been proposed to reduce the area, performance and power costs of ECC [25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%